The effect of a community health worker intervention on public satisfaction: evidence from an unregistered outcome in a cluster-randomized controlled trial in Dar es Salaam, Tanzania - Larson, Elysia; Geldsetzer, Pascal; Mboggo, Eric; Lema, Irene Andrew; Sando, David; Ekström, Anna Mia; Fawzi, Wafaie; Foster, Dawn W.; Kilewo, Charles; Li, Nan; Machumi, Lameck; Magesa, Lucy; et al. (Human resources for health, 2019)
There is a dearth of evidence on the causal effects of different care delivery approaches on health system satisfaction. A better understanding of public satisfaction with the health system is particularly important within the context of task shifting to community health workers (CHWs). This paper determines the effects of a CHW program focused on maternal health services on public satisfaction with the health system among women who are pregnant or have recently delivered.
Gesehen am 01.08.2019